Developing a Low Budget System to Mix, Store, and Deliver CO2-rich Air for Human Research in the Small Liberal Arts College Setting” - Miller, Justin R; Cook-Snyder, Denise R; Buchholz, Kirstyn; Evenhouse, Annika; Nicosia, Tim; Grove, Amanda; Regetz-Mularney, Theresa; Moench, Kelly; Tajnai, Sophia; Miller, Daniel P; et al. (Proceedings of the Wisconsin Space Conference, 2019)
Carbon dioxide (CO2) levels are elevated on the International Space Station, and preliminary reports associate this increased CO2 with headaches, changes in vision, and enhanced emotional experiences, including anxiety. As the duration of space travel extends, improved understanding of the physiologic effects of elevated CO2 exposure is necessary to ensure the capabilities and safety of astronauts. However, studying human breathing has proven difficult at small liberal arts college due to cost and laboratory space constraints. Therefore, the goal of this project is to develop and validate a low budget system that can accurately and dependably mix, store, and deliver enhanced respiratory gases for human research in a liberal arts college setting. Our results provide user-friendly guidelines for building, validating, and maintaining such a system, and broad implementation of this system may increase the quantity and diversity of respiratory research relevant for space travel.